Costs management in maize and soybean production - Artuzo, Felipe Dalzotto; Foguesatto, Cristian Rogério; Leal de Souza, Ângela Rozane; Silva, Leonardo Xavier da (Review of Business Management, 2018)
Purpose – This research aims to identify and analyze the relationship between the elements that make up maize and soybean production costs and the revenue earned from the respective productive activities. Design/methodology/approach – We used production cost data from Conab and the market price of maize and soybean obtained from FAO in our analyses. These data were analyzed from 1997 to 2016. The study is based on the Neoclassical Theory of Firm and its subdivision: Cost Theory. Findings – The data showed that the variables related to the production costs of maize and soybean are associated with the gross revenue ha-1. Therefore, it is possible to predict them from the regression equations. Based in these findings, farmers will have a tool that may be used in making of the best decision when they purchase agricultural inputs. Originality/value – The main contribution of this paper relates to the possibility to predict maize and soybean revenue from the cost variables that are part of the production cost of these commodities. In this context, an interpretation of production costs, analyzing the variables involved in the cost of the crops, and with a consequent evaluation of the information on the gross revenue ha-1, enables information to be obtained for decision-making regarding the agricultural activities.